0138 Pooled uranium miners analysis: goals and challenges. (21st August 2017) - Richardson, David; Kreuzer, Michaela; Fenske, Nora; Sobotzki, Christina; Do, Minh; Demers, Paul; Laurier, Dominique; Rage, Estelle; Schubauer-Berigan, Mary; Tomasek, Ladislav; Samet, Jon; Zablotska, Lydia
Abstract : Epidemiological studies of uranium miners helped to establish radon as a human carcinogen. However, radon remains a leading occupational cause of cancer mortality, and many workers are exposed to radon at levels at which excess risk of lung cancer has been observed in occupational cohort studies. Prior pooled studies of underground miners provided important quantitative estimates of radon-associated lung cancer risk. Recently, efforts have been undertaken to strengthen uranium miner studies to address contemporary occupational safety concerns. New cohorts of underground miners have been enumerated, existing cohorts have been expanded, and follow-up of the major cohorts of miners has been extended substantially. An international collaborative study has been undertaken to combine information from many of the world's most informative cohort studies of uranium miners; the combined study cohort encompasses more than 1 00 000 miners. This talk will describe the major themes of this project, the goals of the collaborators and the challenges that we have encountered to-date. We will describe similarities and differences between findings from these key cohorts and identify some major gaps in current knowledge about radon's effects on human health. Finally, we will discuss how international collaborative studies can strengthen our understanding of risks associated with occupational and environmental radon exposures.